2016
DOI: 10.1016/j.juro.2015.10.174
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Controlled Trial of the Efficacy of External Physical Vibration Lithecbole after Extracorporeal Shock Wave Lithotripsy for a Lower Pole Renal Stone Less Than 2 cm

Abstract: External physical vibration lithecbole was efficacious in assisting the discharge of lower pole renal stone fragments and can be used as an adjunctive method of minimally invasive stone treatment. However, additional investigations are needed to confirm the efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…With the increasing experience and regeneration of equipment, a new device called EPVL was invented in China, which can provide a well-controlled inversion and body position changing from a rotating couch, and also a circled mechanical percussion [32]. With multiple approaches for mechanical percussion and effective percussion could be performed, EPVL was reported to improve the SFR following ESWL and RIRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing experience and regeneration of equipment, a new device called EPVL was invented in China, which can provide a well-controlled inversion and body position changing from a rotating couch, and also a circled mechanical percussion [32]. With multiple approaches for mechanical percussion and effective percussion could be performed, EPVL was reported to improve the SFR following ESWL and RIRS.…”
Section: Discussionmentioning
confidence: 99%
“…As listed in Table 1, a total of 8 prospective studies published from 2001 to 2019 were nally enrolled into the present analysis [29,[32][33][34][35][36][37][38], including 7 RCTs and 1 prospective case control study. 3 studies were multi-center studies (NCT02645708, NCT02643134, one not registered).…”
Section: Characteristics and Quality Of The Included Studiesmentioning
confidence: 99%
“…It is very clear and concise that for any newly designed and introduced technique to be well accepted, it should be first safe and also efficacious. Related with this issue, data obtained from several clinical studies have proved well with high-level evidence that the EPVL is a safe, simple, effective, and non-invasive method to facilitate the spontaneous passage of the residual fragments detected after RIRS or ESWL [2][3][4][5][6]. Of the published data with this system so far, Wu et al [2] were able to demonstrate that EVPL as a supplement to RIRS could be more effective than RIRS alone by shortening the time period for stone clearance, increasing complete stone-free rates with good patient compliance and acceptance.…”
mentioning
confidence: 86%
“…Further supporting these findings, Zhang et al [5] were able to show that the best time to perform EPVL is 3 days after RIRS procedure for the highest stone-free rates at any point in time with meaningfully reduced complications caused by these fragments. Last but not least, in their original studies, Long et al [3], Wu et al [6], and Tao et al [4], all reported well that EPVL could facilitate the spontaneous discharge of residual stone fragments with a meaningfully shortened expulsion time after SWL. Thus all these data clearly indicate that the EPVL system can be regarded as an adjunctive active treatment modality particularly for residual stone fragments after RIRS and SWL procedures in an outpatient service manner.…”
mentioning
confidence: 98%
“…8,9 Recently, a new extracorporeal physical vibrational lithecbole (EPVL) device named Friend-I EPVL (Zhengzhou Fu Jian Da Medical Instrument Co., Zhengzhou, China) has proven to be an effective treatment for upper urinary tract residual calculi. 10,11 The device was approved by the Chinese Food and Drug Administration in 2012. It consists of a stationary vibrator, an adjustable bed, and a mobile vibrator (Fig.…”
Section: Introductionmentioning
confidence: 99%